The results of anterior rectal resection with the formation of a hardware anastomosis in cancer patients - E. N. Kolesnikov; A. V. Snezhko; V. S. Trifanov; M. A. Kozhushko; Yu. A. Fomenko; T. B. Katsieva; R. E. Myagkov; S. V. Sanamyanc; M. A. Averkin; G. Yu. Egorov (Южно-Российский онкологический журнал)
Purpose of the study. A retrospective analysis of the immediate results of performing anterior rectal resections in cancer. Materials and methods. In the Department of Abdominal Oncology No. 1 with a group of X-ray vascular methods of diagnosis and treatment of the clinic of the National Medical Research Centre for Oncology of the Ministry of Health of Russia treatment for rectal cancer operations of anterior rectal resection were performed in 334 patients, while in 143 (42.8 %) cases they were low. As a standard, total mesenteric excision and lymphoid dissection in volume D2 were performed. Combined surgical interventions were performed in 68 (20.4 %) patients for locally spread tumors. As a rule, they were resection in nature and were performed with tumor infiltration of adjacent organs (bladder with ureters, ovaries, uterus, vagina, small intestine, abdominal wall). Colorectal anastomosis using crosslinking devices was formed in all cases, in 316 (94.6 %) cases it was a "side – to-end" junction, in 18 patients – "end-to-end". A preventive proximal intestinal stoma was formed in 73 (21.9 %) cases, where 67 cases it was an ileostomy, and 6 – a transversostomy. The preventive proximal intestinal stoma was not formed among 261 patients. Results. After performing anterior resections for rectal cancer operations, the complications developed in 75 (22.5 %) patients. The most threatening and dangerous complication was the failure of the colorectal anastomosis, which was noted in 12 (3.5 %) cases.This complication occurred in 8.2 % (6 patients out of 73) of preventatively stoma-treated patients, in 2.3 % of patients without a stoma (6 patients out of 261).Conclusion. The use of a preventive proximal intestinal stoma allows you to form a colorectal anastomosis even in the presence of complicated forms of rectal cancer. The number of complications directly referred to the formation of a preventive proximal intestinal stoma is relatively small, but when planning surgery for uncomplicated rectal cancer, the probability of their possible occurrence should be taken into account.